Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1243/09544062jmes1202
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental studies on the steady-state performance of low-speed high-torque hydrostatic drives. Part 1: Modelling

Abstract: In this article the steady-state models of an open-circuit and a closed-circuit hydrostatic transmission (HST) drive have been developed to study their performances. A low-speed high-torque multi-stroke cam plate type radial piston motor is considered for both HST drives. Bondgraph simulation technique has been used to model the drives. The multi-bondgraph representation of the HST drives is presented; it takes into account the compression and expansion phases, which occur sequentially in the hydraulic motor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 6 publications
2
17
0
Order By: Relevance
“…A systematic overview of the hydraulic circuits for the servo-hydraulic power drives presented by Murrenhoff 3 may be useful for the designer to find out the best circuit for a given application. In recent years, Mandal et al 4,5 have proposed models to study the steady-state performance of a speed-controlled open-circuit and a pump-controlled closed-circuit hydrostatic drives with low speed high torque motor. Using the steady-state model, the dynamic performance of the system has been studied by Dasgupta et al 6 In such studies, critical parameters of the pumps and the motor are identified that effect the performance of the drives.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic overview of the hydraulic circuits for the servo-hydraulic power drives presented by Murrenhoff 3 may be useful for the designer to find out the best circuit for a given application. In recent years, Mandal et al 4,5 have proposed models to study the steady-state performance of a speed-controlled open-circuit and a pump-controlled closed-circuit hydrostatic drives with low speed high torque motor. Using the steady-state model, the dynamic performance of the system has been studied by Dasgupta et al 6 In such studies, critical parameters of the pumps and the motor are identified that effect the performance of the drives.…”
Section: Introductionmentioning
confidence: 99%
“…3. The loading circuit provides mainly the viscous load on the hydro-motors (5,12) that is made by adjusting the pressure setting of the proportional pressure relief valve (8) or displacement of the pump (7) of the loading circuit. 4.…”
Section: Discussionmentioning
confidence: 99%
“…Williamson et al [4] have examined the relationship between the efficiency of the pump and the complete hydraulic system using a pump controlled drive used in a front-end loader machine and concluded that when the pump operates at low displacements, it affects the overall efficiency of the system significantly. Mandal et al [5,6] have identified the parameters of the pump and the motor that have significant influence on the characteristics of the closedcircuit hydraulic drive using LSHT motor used in heavy machineries. Also, they have proposed the methodologies to operate the system in most efficient zone.…”
Section: Introductionmentioning
confidence: 99%
“…16) the difference between the experimental and estimated pressure is less. It may be due to the reduced leakage flow from the pump [9,10].…”
Section: Estimation Of Pressures Obtained From the Ekfmentioning
confidence: 99%
“…In this paper, MATLAB-Simulink has been used to model the hydraulic drive system [8][9][10][11] and study its observability [12][13][14][15]. In the next section, the test set-up has been described.…”
Section: Introductionmentioning
confidence: 99%